463 - Evaluating the Implementation of a Memory Clinic using the RE-AIM model. The experience of the "Memory and Neuropsychiatry Clinic" in Hospital del Salvador, Chile: Implementation of a Memory Clinic in Chile. (October 2020) - Leon, T.; Castro, L.; Mascayano, F.; Lawlor, BA.; Slachevsky, A.
Abstract: The prevalence of dementia in Chile is 1.06 %, meaning that over 200, 000 people are affected. In 2017, the Ministry of Health launched the National Plan of Dementia, which proposed establishing a range of health-care services from primary care to Memory Units (MU). MUs have emerged as a new health care service composed of multidisciplinary teams with the goal of improving diagnosis and management of dementia patients. The creation and implementation of a MU should take into consideration the organization of a particular healthcare system. In this context, the evaluation of a Chilean MU might provide information for the standardization and replication of such a health service on a regional basis. The objective of this paper was to evaluate the implementation processes of a MU using the RE-AIM model, a multi-component model aimed to assist the evaluation of the implementation of ongoing programs. Regarding "R" (Reach): from March 2018 up to June 2019, a total of 510 patients were referred and assessed at the Hospital del Salvador. Most patients came from primary care (51.9 %) and from outpatient services at the Hospital (39.2 %), particularly from the Neurology (63.3%) and Psychiatry (16.0 %) departments. We estimated that the MU assessed 5.39% of dementia patients living in the area of referral. In relationship with "E" (Effectiveness): of patients evaluated by the MU, 60 (11%) were discharged. Of these, 41 (66%) were referred to primary health care, 9 (17%) to other outpatient services, 6 (10%) to a specialized mental health care center, and 4 (7%) to a daycare center. Due to the short lifespan of our MU, no other RE-AIM dimensions could be evaluated yet. This was the first evaluation of the implementation of a MU in Chile as part of the Chilean Dementia Plan. It showed that it is possible to implement a MU in a Latin American country and improve access to dementia diagnosis, management, and treatment. Ongoing challenges include continuing to collect clinical data, creating research projects as part of the MU, and developing a MU protocol that can be adopted elsewhere in Chile and other Latin American countries.